New colonoscope technology: impact on image capture and quality and on confidence and accuracy of endoscopy-based polyp discrimination - Bade, Kaely; MacPhail, Margaret E.; Johnson, Cynthia S.; Kahi, Charles J.; Rex, Douglas K. (Endoscopy, 2014)
Background and study aims: A newer colonoscope series has optical magnification and improvement in image freezing function. We aimed to assess the impact on image capture, image quality, and polyp discrimination.Patients and methods: In consecutive patients undergoing outpatient colonoscopy images of colorectal polyps were taken with Olympus 190 or 180 series instruments. The number of image captures needed to obtain an adequate image, quality of stored images, proportion of polyps with a high confidence estimate of likely histology, and accuracy of interpretations were compared.Results: An acceptable image at the first attempt was obtained in 97.3 % of photos with the 190 device vs. 83.8 % with the 180 instrument (P < 0.001). In the 190 group narrowband imaging (NBI) provided high confidence readings in 9 % more cases than in the 180 group, but did not improve accuracy of polyp categorization. The quality of the stored images was judged better for the 190 device. However, when images that had provided high confidence estimates of polyp histology were re-interpreted later by the original endoscopist, there was agreement with the original interpretation for > 98 % of polyps in both the 180 group and the 190 group. A second endoscopist agreed with the original high confidence interpretations for 90 % of polyps imaged with either the 180 or the 190 scope.Conclusion: The new colonoscope had less image blurring, improved subjective quality of stored images, and increased the proportion of high confidence endoscopic estimates of polyp histology, but did not improve accuracy in estimating polyp histology.